An overview of structure, function, and regulation of pyruvate kinases. (12th August 2019) - Schormann, Norbert; Hayden, Katherine L.; Lee, Paul; Banerjee, Surajit; Chattopadhyay, Debasish
Abstract: In the last step of glycolysis Pyruvate kinase catalyzes the irreversible conversion of ADP and phosphoenolpyruvate to ATP and pyruvic acid, both crucial for cellular metabolism. Thus pyruvate kinase plays a key role in controlling the metabolic flux and ATP production. The hallmark of the activity of different pyruvate kinases is their tight modulation by a variety of mechanisms including the use of a large number of physiological allosteric effectors in addition to their homotropic regulation by phosphoenolpyruvate. Binding of effectors signals precise and orchestrated movements in selected areas of the protein structure that alter the catalytic action of these evolutionarily conserved enzymes with remarkably conserved architecture and sequences. While the diverse nature of the allosteric effectors has been discussed in the literature, the structural basis of their regulatory effects is still not well understood because of the lack of data representing conformations in various activation states. Results of recent studies on pyruvate kinases of different families suggest that members of evolutionarily related families follow somewhat conserved allosteric strategies but evolutionarily distant members adopt different strategies. Here we review the structure and allosteric properties of pyruvate kinases of different families for which structural data are available.